Features of Başören (Gürün-Sivas) sedimentary and remobilized barite deposits - Bölücek, Cermal; Akgül, Muharrem; Sa?iro?lu, Ahmet (My University, 2004)
The Başören barite deposits occur in the Middle Albian-Campanian Yaniktepe Formation and at two localites namely Belpinari and Ardiçli Tepe. The basic component of the Yaniktepe Formation is limestone and includes chert nodules in lower levels. The Belpinari barite formations occur as matrix among chert nodules, chert and limestone fragments in cherty lower levels. Ardiçli Tepe barite masses fill a fracture zone and massive in the center and bear limestone fragments and inclusions along the margins of the zone. Barite formations are monomineralic, as fine grained primary barite and coarse grained-radial diagenetic barite. Barite crystals also show polysentetic twin. Barite concretions are seen in some samples. Barit formations are composed of dominantly barite minerals, and quartz and calcite gangue are in low amounts. At both locations the barit concentrations have characteristically low trace element contents. Field and microscopic data, mineral paragenesis and trace element geochemistry all indicate that Belpinari barite formations have sedimentary in origin and remobilized fractions of these formations are responsible for Ardiçli Tepe barites.
Başören (Gürün-Sivas) sedimanter ve yeniden hareketlenmiş barit yataklarinin özellikleri
Keywords: Başören; Chert nodules; Sedimentary barite; Yaniktepe formation